To the analysis of methods of calculation of stability of use and their classification - Sirenko, Anatolii P. (Kyiv National University of Construction and Architecture, 2019)
The problem of assessing the stability of slopes is quite relevant in the development of mineral deposits in an open way, in hydraulic engineering and transport, industrial and civil engineering, as well as in other areas of human activity. Attempts to obtain the correct method of calculation led to the emergence of a large number of methods, methods of calculation and calculation schemes: their diversity is explained by the number of assumptions used by researchers to justify the calculation scheme and stability conditions. The task of determining the parameters of a steady slope or bearing capacity of the base in most cases is statically uncertain. Therefore, for the determination of unknown reactions, the authors put forward additional conditions (assumptions). The variety of existing methods for calculating the stability of slopes caused the need to classify them by one or another feature. Based on a detailed analysis of work in this area, four groups of basic assumptions put forward by researchers for substantiation of the calculation scheme for calculating the stability of slopes, obtaining stability conditions (equilibrium) of the shift prisms, the selection of the shape and position of the weakest surface of slip in the slopes were identified. These are assumptions such as: about the condition of the boundary stress state at each point of the bias prism (the method of the boundary stress state); about the distribution of normal reactions along the surface of the slip (methods of a monolithic compartment of collapse, that is, when considering the balance of the prism of the shear completely); the ratio of tangential and normal reactions at the lateral sides of the compartments (the reaction is horizontal, inclined or marginal rejected); in relation to the shape and position (geometry) of the potential (weakest) surface of the slide. In conclusion, it was concluded that the method of the boundary stress state is most useful for preventing collapses, then studying the shape of slopes and external loading, at which a possible collapse. The method of boundary equilibrium, in turn, is desirable to use for the analysis of a strained state of landslides.